Fresh Produce E-Commerce and Online Shoppers' Purchase Intention. Issue 6 (2nd November 2021) - Zhao, Kaiqi; Shi, Hongxu; Zhang, Yu Yvette; Sheng, Jiping
Abstract: The development of the Internet has provided many opportunities for electronic commerce, and many e-commerce companies like Alibaba have achieved great success. Fresh produce industry has also attempted to step into e-commerce during the past decade. It is important for e-commerce to understand customers' demands in this new market in order to make profits. In this research we conducted a market survey to investigate the market situation of Chinese fresh produce e-commerce. Consumer attitudes and behaviors toward online shopping for fresh fruits were evaluated. A logit model was used to identify potential factors that may have impact on consumers' purchase intention. Results show that women are more likely than men to shop online; other factors such as influence from friends, income, product quality, food labels, packaging, and payment security can also affect online shoppers' purchase intention.